2013
DOI: 10.1080/15325008.2013.801058
|View full text |Cite
|
Sign up to set email alerts
|

Constant Voltage-clamping Bipolar Pulse Current Source for Transient Electromagnetic System

Abstract: This article proposes a bipolar pulse current source for the transient electromagnetic system. This current source consists of a full-bridge converter circuit, a constant voltage-clamping circuit, and a damping-snubber circuit. Bipolar pulses are generated by the full-bridge converter circuit. During the rising edge of the pulse current, the high voltage generated by the constant voltage-clamping circuit is added to the load, which will enhance the rising speed of the pulse current and help the current quickly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The geometry of TEM waveforms, including the current pulse width, edge steepness, edge linearity, and the current magnitude, has become the focus of research studies for these years (Fitterman and Anderson ; Fu, Zhou and Tai ; Feng, Wang and Lian ; Dennis and Cull ; Zhao et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The geometry of TEM waveforms, including the current pulse width, edge steepness, edge linearity, and the current magnitude, has become the focus of research studies for these years (Fitterman and Anderson ; Fu, Zhou and Tai ; Feng, Wang and Lian ; Dennis and Cull ; Zhao et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Zhao et al . () made an effort to steepen the rising edge of the transmitting current. We have also carried out the design and experiments to provide a current of 20 A for a transmitting coil of 2.1 mH and obtained a rise time less than 200 μs, which will help promote the field application of the results in this paper in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…When DC-DC converters are used, it releases electromagnetic emissions at a very high switching frequency and thus forms main sources of EMI. EMI is any man-made or natural electromagnetic disturbance or signal that causes an unacceptable response or malfunctioning of any electrical or electronic device or system [5][6][7]. Although such techniques as EMI filters and shielding are available to mitigate the EMI, they work as a remedy.…”
Section: Introductionmentioning
confidence: 97%
“…The switching power loss reduction in inverters is one of the most important aspects of PWM strategies, and hence, much research has been reported to decrease the switching power losses [9][10][11][12][13][14][15]. However, there has been no thorough research reported for the ZSI switching power loss reduction.…”
Section: Introductionmentioning
confidence: 98%